Tinjauan Keakuratan Kode Diagnosis Gastroenteritis Pada Pasien Rawat Inap Berdasarkan ICD-10 Dan Hasil Pemeriksaan Laboratorium Di RSUD Banjarbaru Pada Triwulan III Tahun 2013 - Dion Angger Priyatama; Deasy Rosmala Dewi; Ratna Auliyana; STIKES Husada Borneo; Alumni STIKES Husada Borneo (Jurnal Kesehatan Indonesia, 2015)
Coding is a key of health treatment organization. The accurate coding is a very important thing in data organizing, reimbursement, and another problems. Inaccuracy of Gastroenteritis diagnosis code found in Banjarbaru hospital which caused by there is no recheck toward additional information such as laboratory report in coding process. This research has purpose to confirm the accuracy of Gastroenteritis diagnosis code of inpatient based on ICD-10. This research use descriptive analysis with 106 medical records of inpatient of Gastroenteritis diagnosis case as the sample. Data collection methods which used in this research are observation and interview. This research use univariate analysis and the result presented in tabulation and text explanation. The result of research shows that only 2,83% Gastroenteritis code is accurate and 97,17% is not. The output of Gastroenteritis diagnosis code use as RL 4a report, disease index, top 10 of common disease list, and hospital activity/service data. Human resouces who involved in Gastroenteritis diagnosis coding process are manager of medical record department, inpatient coder, and doctor.